A multicriteria approach for evaluating high temperature hydrogen production processes. (1st January 2011) - Galzim, Ouassim; Mansilla, Christine; Giaconia, Alberto; Poitou, Sabine; Hinkley, Jim; Ebbesen, Sune Dalgaard; Gasik, Michael; Gilardi, Thierry; Le Naour, François; Graf, Daniela; Roeb, Martin; Sattler, Christian; et al.
Hydrogen demand has already significantly increased due to the industry needs. Mature technologies based on fossil fuels are not satisfactory due to greenhouse gas concerns. In response, a range of advanced processes are being developed throughout the world. Within the 'International Energy Agency – Hydrogen Implementing Agreement – Task 25', a multicriteria methodology was developed for the evaluation of high temperature hydrogen production processes. The aim is to guide R&D strategy by highlighting to which extent the processes may appear promising. The method that was developed is based on the elimination and choice translating the reality (ELECTRE). This study has conducted a first pass application to hydrogen production and highlights the importance of significant weightings and discriminating criteria. Decision makers can apply this method to extract their own subset of processes from the alternatives, according to their system of values defined through the selection of criteria and the associated weights.